GAMBARAN BERBAGAI MEREK HAND SANITIZER DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Staphylococcus Aureus SECARA IN-VITRO - elbetan, sabri (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Clean and Healthy Living Behaviour (PHBS) as an improvement in public health, one of which is washing hands or maintaining hand hygiene. Can be done in addition to using clean water can also use Hand sanitiser. In the community there are many brands of hand sanitiser, and this needs to be proven for its effectiveness. One of the things that can be done is to test its effectiveness on a laboratory scale. Bacteria that are commonly found as floranormal bacteria are Staphylococcus aureus. On a hospital scale this bacterium becomes a nosocomial problem as a methicillin-resistant bacterium or MRSA. The purpose of the study was to determine the effectiveness of various brands of hand sanitiser against the growth of Staphylococcus aureus ATCC 29213 bacteria. Test method using Kirby Baure with Mannitol Salt Agar media. Samples included 3 brands of Hand sanitiser which were carried out with 5 repetitions. The results of the study were that the 3 Hand sanitisers tested had various inhibition zones in inhibiting the growth of Staphylococcus aureus bacteria. The results of the Hand sanitizer inhibition test against the growth of Staphylococcus aureus, which is more effective is Hand sanitiser A than B and C, with a diameter of 19.66 mm, std. deviation 2.66 which indicates that type A Hand sanitiser is more effective and the distribution of its influence is more evenly distributed. Normality test results obtained Sig value. >0.05 the data is normally distributed, the results of the normality data test value Sig. >0.05 homogeneous data variance, One Way Anova test Sig. <0.05 there is a real difference, Post Hoc test results Hand sanitizer B and C Sig value. <0.05 there is a real difference.